Prednosti navarjanja s strženskimi žicami - Kejžar, Rajko (Kovine zlitine tehnologije, 1997)
Cored wires combine advantages of manual arc welding with covered electrodes and those of semiautomatic and automatic welding processes with solid wires in various shielding media, i.e. gases and fluxes. They are produced in two ways, i.e.: a) by drawing filled-in tubes and b) by folding of a metal strip into a U-form which is to be filled with metals and minerals, and by subsequent shaping of the wire. Cored wires have practically the same diameters as solid wires. Their applicability to welding devices (MIG/MAG and SAW) is equal to solid wires. Cored-wires, however, are very sensitive to the feeding technique of welding machines because there is a risk of opening of the folded wire and of pouring out of the core into the house package, which leads to a nonuniform feeding and finally to a stand-still during welding. Devices for welding with cored wires should have a separate feeding device for wires made of a strip. Owing to a very simple application, cored wires made of a tube are very suitable for welding and surfacing in industry. With a filling ratio of 30% with the above-mentioned wires, very favourable results are obtained also in surfacing of stronger loaded, wear-resistant claddings.
Keywords: varjenje; navarjanje; žice strženske; legiranje navara; cevi legirane; uporabnost žic; naprave varilne; MIG-MAG; EPP; strženske žice; legiranje; jekla; zlitine